Acervo construido por futuros maestros de inglés y francés en su práctica en escuelas rurales - Viafara González, John Jairo; Pachón Achuri, Vitalia (Colombian Applied Linguistics Journal, 2021)
This qualitative case study included prospective English and French teachers. They were part of a Colombian School of languages which associated with primary rural schools at neighboring municipalities. Employing surveys and semi structured interviews, researchers explored how participants’ pedagogical experiences at rural schools shaped their knowledge construction. The study found that pre-service teachers’ practicums in these rural contexts allowed them to reexamine previously learnt foreign language teaching principles as they considered language use purpose, mother tongue use in classrooms and the integration of nontraditional topics in their teaching. Likewise, participants incorporated general pedagogy principles into their jobs, sought to encourage their students to develop intercultural abilities and to adapt their instructional practices to the Escuela Nueva approach. Pedagogical implications highlight the need to include socio-cultural and critical perspectives in foreign language pre-service teacher education curriculum development.